Penetrance and the Healthy Elderly - Lacaze, Paul (Genet Test Mol Biomarkers, 2017)
The variable penetrance of pathogenic variants (PVs) represents a major challenge to the field of human genetics, often complicating clinical decision-making and risk management. Nonpenetrance, the detection of PVs in the absence of disease manifestation, is a common phenomenon, yet, we know very little about the underlying factors, which may protect some individuals and not others. Placing a new focus on the genomic study of the healthy elderly may be pivotal for advancing our understanding of penetrance. Studying those who remain unaffected late into life, despite harboring known genetic risk variants, could provide important insights into disease mechanisms and ultimately inform clinical care, yet, it has received relatively little attention as a research strategy. The ever increasing use of sequencing technology is further driving the requirement to understand the penetrance of ascertained variants. The ASPREE Biobank of Healthy Ageing provides a unique opportunity to address this area of need. DNA has been collected from a cohort of over 14,000 healthy elderly individuals aged 70 years or older enrolled in an aspirin clinical trial. The ASPREE cohort represents a healthy reference population ascertained without the typical biases of a genetic study. The cohort is depleted of expressed monogenetic disease, yet will contain hundreds of elderly individuals with known PVs in clinically actionable genes. Investigating this population along with other cohorts of the healthy elderly will provide critical new knowledge into the penetrance of actionable variants as a foundation for informing clinical care.